Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3389/fevo.2019.00195
|View full text |Cite
|
Sign up to set email alerts
|

Design Implications for Surveys to Monitor Monarch Butterfly Population Trends

Abstract: The Iowa Multiple Species Inventory and Monitoring (MSIM) Program includes a protocol for monitoring butterfly density on conservation lands using transects. Most data are collected from sites chosen randomly; additional sites are chosen non-randomly for other reasons. We analyzed a 12-year dataset for monarchs to address how density (per 50 m 2 transect section) responded to site selection (random vs. non-random), latitude, and measures of the amount of milkweed and canopy cover on survey transects. Between 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…The high milkweed density documented in this study in Minnesota (2,052 plants/ha by IMMP (834 plants/ac); 1,527 plants/ha (620 plants/ac) by Rapid Assessment) confirm that roadside rights-of-way can provide significant amounts of breeding habitat for monarchs (Kasten et al, 2016). And, adult monarch numbers are associated with percent cover of milkweed (Kinkead et al, 2019) and milkweed abundance has been associated with adult monarch abundance (e.g., Zalucki and Lammers, 2010;Pleasants and Oberhauser, 2013). Converted into linear miles of interest to road managers, for the average rightof-way width we surveyed (9.43 m), this is 2,316-2,641 milkweed plants/mile (using the range of IMMP and RA estimates).…”
Section: Discussionsupporting
confidence: 63%
“…The high milkweed density documented in this study in Minnesota (2,052 plants/ha by IMMP (834 plants/ac); 1,527 plants/ha (620 plants/ac) by Rapid Assessment) confirm that roadside rights-of-way can provide significant amounts of breeding habitat for monarchs (Kasten et al, 2016). And, adult monarch numbers are associated with percent cover of milkweed (Kinkead et al, 2019) and milkweed abundance has been associated with adult monarch abundance (e.g., Zalucki and Lammers, 2010;Pleasants and Oberhauser, 2013). Converted into linear miles of interest to road managers, for the average rightof-way width we surveyed (9.43 m), this is 2,316-2,641 milkweed plants/mile (using the range of IMMP and RA estimates).…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have identified the importance of nectar plants as a component of monarch habitat (Stenoien et al, 2016;Thogmartin et al, 2017a,b;Kinkead et al, 2019), and have proposed that a loss of nectar plant resources could be a significant contributor to increased mortality during migration (Agrawal and Inamine, 2018). The general lack of data on monarch habitat as a whole (milkweed plus nectar plants) makes studies like ours even more necessary.…”
Section: Blooming Plant Frequency and Establishmentmentioning
confidence: 79%
“…We are aware that a prior argument against using evidence from non-random, citizen science monitoring programs such as NABA, is that they provide misleading trends, because people tend to monitor where they know butterflies would be present (Pleasants et al 2015, Pleasants et al 2017, Kinkead et al 2019). It has also been argued that losses of milkweed in the agricultural fields of the Midwest has "shifted" adults away from these areas and into the more pristine monitoring sites (Pleasants et al 2015, Pleasants et al 2017, which could artificially inflate abundance at these sites.…”
Section: Resultsmentioning
confidence: 99%